2022
DOI: 10.1088/1755-1315/998/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

The use of CFD as the design tool for designing a gravitational water vortex turbine

Abstract: Finite Element Analysis is commonly used for product designer to visualize the structural analysis of a product. Not much works done by these designers using Computational Fluid Dynamic, CFD due to the complexity of the application. In this study, the dynamic of the water flow within the turbine had been predicted as the preliminary design steps. Several significant parameters had been reviewed and tested using CFD tool to give better insight of the important components of the turbine on its performance, in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Nishi et al [40] conducted a study on the influence of flow rates on the performance of a GWVHT system by conducting experiments and free surface flow analysis and found that the effective head and turbine efficiency increased as the flow rate increased; hence, the turbine output increased at a rate greater than the increase rate of the flow rate. Nazarudin et al [109] carried out Solidwork simulations on the conical basin using the inlet velocities of 5 m/s, 9.9 m/s, and 13 m/s to study the effect on the outlet velocity, pressure, and vorticity. They noted that the the tangential velocity was higher than the radial velocity; the outlet velocity varied linearly with the inlet velocity, with the maximum outlet velocities of 17.09 m/s, 33.79 m/s, and 44.37 m/s, respectively; the corresponding pressures were 159 kPa, 618 kPa, and 107 kPa, respectively, and there was high pressure at the walls and decreased towards the outlet; the corresponding vorticities were 48.28 m/s, 91.66 m/s, and 120 m/s, respectively, and vorticity was affected by d/D (where d and D are the diameters of the discharge hole and the basin); vorticity decreased towards the centre, and it was weak near the blades and was linear with radius.…”
Section: Vortex Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nishi et al [40] conducted a study on the influence of flow rates on the performance of a GWVHT system by conducting experiments and free surface flow analysis and found that the effective head and turbine efficiency increased as the flow rate increased; hence, the turbine output increased at a rate greater than the increase rate of the flow rate. Nazarudin et al [109] carried out Solidwork simulations on the conical basin using the inlet velocities of 5 m/s, 9.9 m/s, and 13 m/s to study the effect on the outlet velocity, pressure, and vorticity. They noted that the the tangential velocity was higher than the radial velocity; the outlet velocity varied linearly with the inlet velocity, with the maximum outlet velocities of 17.09 m/s, 33.79 m/s, and 44.37 m/s, respectively; the corresponding pressures were 159 kPa, 618 kPa, and 107 kPa, respectively, and there was high pressure at the walls and decreased towards the outlet; the corresponding vorticities were 48.28 m/s, 91.66 m/s, and 120 m/s, respectively, and vorticity was affected by d/D (where d and D are the diameters of the discharge hole and the basin); vorticity decreased towards the centre, and it was weak near the blades and was linear with radius.…”
Section: Vortex Dynamicsmentioning
confidence: 99%
“…In the 39 parametric studies (including optimisation studies), 19 involve basins, 25 involve turbines, and 9 involve channels, while in the remaining non-parametric studies, only 9 involve basins, 12 involve turbines, and 3 involve channels. It should be noted that 23 publications did not involve (or provide information on) any of these three main components at all, which are mainly some case studies and/or feasibility studies [24,31,40,[50][51][52][53]59,60,82,91,94,96,97,101,104,105,109], validation studies [48,66], analytical models [41,67,95], and concept designs [64,104]. It should also be noted that some publications involve more than one main component [23,36,37,46,47,62,77,79,80,85,110] and the thesis [114] involves all three main components.…”
Section: Review Of the Past Studies On The Main Components Of Gwvht S...mentioning
confidence: 99%
“…This work explores all aspects of the turbine including rotation speed, displacement, pressure, and breaking point under various conditions. Nazarudin et al (2022) reviewed and tested various significant parameters using the CFD analysis to get a clear picture of the prime components of the turbine on its performance, based on the pressure, velocity, and water vorticity. Another work done by Bajracharya et al (2018) uses FEA simulation and CFD to analyze the interaction of the fluid with the turbines during operation.…”
Section: Introductionmentioning
confidence: 99%